2021
DOI: 10.15419/bmrat.v8i4.670
|View full text |Cite
|
Sign up to set email alerts
|

In vivo study of wound healing processes in Sprague-Dawley model using human mesenchymal stem cells and platelet-rich plasma

Abstract: Introduction: Mesenchymal stem cells (MSCs) and platelet-rich plasma (PRP) have a potential role in improving wound healing processes. This experimental study aims to compare PRP and MSCs to promote the wound healing process in the animal burn wound model. Methods: PRP from venous blood and MSCs from lipoaspirates were isolated from six donors. Saline solution was used as control while PRP and MSCs as treatment groups were injected to second-degree burn wounds in the backs of 10 male Sprague-Dawley rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…A total of 24 studies reported between 2013 and 2021 satisfied the inclusion criteria for the meta‐analysis among the 345 distinctive reports. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 This meta‐analysis study included 400 animals with burn wounds at the beginning of the study; 211 were using stem cells treatment, and 189 were controlled. All studies evaluated the effect of stem cells treatment in managing burn wounds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 24 studies reported between 2013 and 2021 satisfied the inclusion criteria for the meta‐analysis among the 345 distinctive reports. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 This meta‐analysis study included 400 animals with burn wounds at the beginning of the study; 211 were using stem cells treatment, and 189 were controlled. All studies evaluated the effect of stem cells treatment in managing burn wounds.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 studies reported between 2013 and 2021 satisfied the inclusion criteria for the meta‐analysis among the 345 distinctive reports 24‐47 . This meta‐analysis study included 400 animals with burn wounds at the beginning of the study; 211 were using stem cells treatment, and 189 were controlled.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, MSCs are better than PRP in increasing cell differentiation. 49 The timing of MSCs transplantation is also an important factor that may determine the survival of stem cells in the wound bed. Inflammatory response activated in a burn wound might worse the damage cells and tissues.…”
Section: Dpscsmentioning
confidence: 99%